Particulate Matter Pollution Remains a Threat for Cardiovascular Health: Findings From the Global Burden of Disease 2019 - Mahsa Moradi; Amir Hossein Behnoush; Mohsen Abbasi-Kangevari; Sahar Saeedi Moghaddam; Zahra Soleimani; Zahra Esfahani; Mohammadreza Naderian; Mohammad-Reza Malekpour; Nazila Rezaei; Mohammad Keykhaei; Shaghayegh Khanmohammadi; Hamed Tavolinejad; et al. (Journal of the American Heart Association, 2023)
Particulate matter (PM) pollution is a significant risk factor for cardiovascular diseases, causing substantial disease burden and deaths worldwide. This study aimed to investigate the global burden of cardiovascular diseases attributed to PM from 1990 to 2019. We used the GBD (Global Burden of Disease) study 2019 to investigate disability-adjusted life-years (DALYs), years of life lost (YLLs), years lived with disability (YLDs), and deaths attributed to PM as well as its subgroups. It was shown that all burden measures' age-standardized rates for PM were in the same decreasing trend, with the highest decline recorded for deaths (-36.7%). However, the all-age DALYs increased by 31%, reaching 8.90.167emmillion in 2019, to which YLLs contributed the most (8.20.167emmillion [95% uncertainty interval, 7.3 million–9.2 million]). Men had higher deaths, DALYs, and YLLs despite lower years lived with disability in 2019 compared with women. There was an 8.1% increase in the age-standardized rate of DALYs for ambient PM; however, household air pollution from solid fuels decreased by 65.4% in the assessed period. Although higher in men, the low and high sociodemographic index regions had the highest and lowest attributed YLLs/YLDs~ratio for PM pollution in 2019, respectively. Although the total age-standardized rate of DALYs for PM-attributed cardiovascular diseases diminished from 1990 to 2019, the global burden of PM on cardiovascular diseases has increased. The differences between men and women and between regions have clinical and policy implications in global health planning toward more exact funding and resource allocation, in addition to addressing inequity in health care access.
Keywords: 320; air pollution; cardiovascular diseases; global burden of disease; particulate matter; sociodemographic index